The Alternative Peer Group: A Developmentally Appropriate Recovery Support Model for Adolescents. Issue 2 (April 2016) - Nash, Angela; Collier, Crystal
Abstract : Abstract: Recovery as the goal for substance use disorder treatment has been a key component of the Substance Abuse and Mental Health Services Administration's mission for the past decade. Consistent with their mission, there is a call for research and development of recovery-oriented systems of care to support affected individuals through all stages of the recovery process. Evidence is emerging to support recovery practice and research for adults, but recovery-oriented models for adolescents are scant. The Alternative Peer Group (APG) is a comprehensive adolescent recovery support model that integrates recovering peers and prosocial activities into evidence-based clinical practice. Employing APG participants' own words, this article will describe the essential elements and three theoretical frameworks underlying the APG model to illustrate how the APG serves as a developmentally appropriate recovery support service for adolescents with substance use disorder.